Methylation From DNA, RNA and Histones to Diseases and Treatment - Dricu, Anica (IntechOpen, 2012)
Alterations in the normal DNA methylation processes are known to have major consequences for embryonic development and are associated with congenital defects, autoimmunity, aging and malignant transformation. The main purpose of this book is to provide information about the importance of methylation mechanisms in human health and disease. The book, covers the basic mechanism of DNA and protein methylation, aiming at the advanced undergraduate and graduate biomedical students and researchers working in the epigenetic area. The textbook chapters provide background as well as advanced information in the methylation area. On the other hand, it provide readers with both classical and relevant recent discoveries that have been made in the field, pointing out pathways where questions remain.